DOI: 10.1007/978-3-211-76589-0_19
|View full text |Cite
|
Sign up to set email alerts
|

Combined treatment using CEA and CAS for carotid arterial stenosis

Abstract: In this study we report our surgical results of CAS and CEA for carotid stenosis and suggest an appropriate treatment strategy for patients with high risks such as bilateral carotid stenosis or medical risk factors. From January 2001 to December 2005 we surgically treated 182 patients with carotid stenosis. Seventy-nine lesions were treated by CEA and 145 by CAS, respectively. Although CEA was considered the first choice for severe carotid stenosis, CAS was chosen for treatment when CEA was considered a higher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Another multicenter cohort study in Japan reported that 25 of 1596 patients (1.6%) had new neurologic symptoms due to ipsilateral ischemic stroke and 18 patients (1.1%) experienced lower cranial nerve palsy 30 days after CEA. 15 In a recent single-institution Japanese study, Tsukahara et al 16 In the present study, we measured CBF by SPECT immediately after CEA to identify postoperative hyperperfusion. We detected postoperative hyperperfusion in 8 patients (5.6%), most of whom had symptomatic ICA stenosis.…”
Section: Discussionmentioning
confidence: 98%
“…Another multicenter cohort study in Japan reported that 25 of 1596 patients (1.6%) had new neurologic symptoms due to ipsilateral ischemic stroke and 18 patients (1.1%) experienced lower cranial nerve palsy 30 days after CEA. 15 In a recent single-institution Japanese study, Tsukahara et al 16 In the present study, we measured CBF by SPECT immediately after CEA to identify postoperative hyperperfusion. We detected postoperative hyperperfusion in 8 patients (5.6%), most of whom had symptomatic ICA stenosis.…”
Section: Discussionmentioning
confidence: 98%
“…The treatment of CAS includes three modalities: Medical management, carotid artery angioplasty and stenting, and CEA ( 26 ). However, there are doubts regarding the efficacy of carotid artery angioplasty and stenting, and CEA, in specific patients ( 27 29 ). Previous studies have aimed to identify novel treatments and medications for atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%